2020
DOI: 10.3346/jkms.2020.35.e233
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Characteristics of Patients with Liver Cirrhosis Visiting a Tertiary Hospital over 15 Years: a Retrospective Multi-Center Study in Korea

Abstract: Background: Liver cirrhosis has become a heavy burden not only for patients, but also for our society. However, little is known about the recent changes in clinical outcomes and characteristics of patients with cirrhosis-related complications in Korea. Therefore, we aimed to evaluate changes in characteristics of patients with liver cirrhosis in Daegu-Gyeongbuk province in Korea over the past 15 years. Methods: We retrospectively reviewed the medical records of 15,716 liver cirrhotic patients from 5 university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…A total of 171 cases did not present COTB in cirrhosis at the time of admission, but bleeding symptoms were prevalent during the follow-up ( Table 1 ), which was consistent with the main complications of cirrhosis described in the Chinese textbook such as bleeding esophageal varices, cholelithiasis, infection, liver encephalopathy, and PVT or spongiform changes. Notably, other studies have reported a wide variety of complications in liver cirrhosis patients, which might be attributed to the different races and geographical locations of the study populations [ 2 , 26 , 27 ]. The three major complications occurring before and after the bleeding treatments were consistent, suggesting that bleeding treatment did not affect these complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 171 cases did not present COTB in cirrhosis at the time of admission, but bleeding symptoms were prevalent during the follow-up ( Table 1 ), which was consistent with the main complications of cirrhosis described in the Chinese textbook such as bleeding esophageal varices, cholelithiasis, infection, liver encephalopathy, and PVT or spongiform changes. Notably, other studies have reported a wide variety of complications in liver cirrhosis patients, which might be attributed to the different races and geographical locations of the study populations [ 2 , 26 , 27 ]. The three major complications occurring before and after the bleeding treatments were consistent, suggesting that bleeding treatment did not affect these complications.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the incidence rate of viral hepatitis-induced liver cirrhosis is significantly higher in the Chinese population than that in Western countries. Undoubtedly, liver cirrhosis has become one of the leading public health issues globally [ 2 ]. Although an early stage of liver cirrhosis can be cured, however, the later stage of the disease can lead to a spectrum of secondary complications, including progressive portal hypertension, systemic inflammation, liver failure, liver encephalopathy, and primary liver cancer [ 3 ], resulting in poor treatment outcomes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Easy access to healthcare through universal health coverage, availability of a national health examination, which includes AST/ALT and GGT [ 39 ], and a national liver cancer surveillance program might increase the chances of detecting clinically significant LC. In addition, the definition of LC according to ICD 10 codes has been accepted as sufficiently reliable and has been used in previous studies [ 22 , 40 ], although external validation with clinical data has not been conducted. Finally, there may be a recall bias and impreciseness regarding the self-reported questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of cirrhosis cases due to HCV and HBV infection declined (from 59% to 40% and from 14% to 9%, respectively), although these remained the largest contributors. In another study in 15,716 patients with cirrhosis at five university hospitals in South Korea between 2000 and 2014, the proportion of cirrhosis cases due to NAFLD, alcohol consumption and HCV infection increased over the study period 57 . However, the study periods of both of these studies were before the widespread availability of DAA therapy for HCV infection, which is likely to reduce the proportion of cirrhosis cases that are due to HCV infection over time.…”
Section: Trends In the Aetiology Of Cirrhosismentioning
confidence: 97%